1992
DOI: 10.1111/j.1471-0528.1992.tb14465.x
|View full text |Cite
|
Sign up to set email alerts
|

the treatment of intrahepatic cholestasis of pregnancy by dexamethasone

Abstract: Objective To investigate whether dexamethasone supression of fetoplacental oestrogen production can reduce obstetric cholestasis. Design Observational study. Setting Department of Obstetrics and Gynaecology, University of Tampere, Finland. Subjects 10 women, at between 28 and 37 weeks gestation, with intrahepatic cholestasis of pregnancy. Interventions Treatment with 12 mg oral dexamethasone daily for 7 days, after which the therapy was gradually discontinued over 3 days. Main out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 9 publications
0
27
1
2
Order By: Relevance
“…Efficacy in reducing maternal serum bile acid levels seems to be an important quality when choosing a drug for the treatment of ICP because bile acid levels have been demonstrated to have a dose-dependent association with fetal complication rates. 10 In conflict with a previous report on dexamethasone therapy in ICP women, 16 we found the effects on pruritus and biochemical markers of cholestasis to be transient in the dexamethasone group. A rapid decrease in pruritus and bile acids was seen after the first week of treatment, but was followed by an increase.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Efficacy in reducing maternal serum bile acid levels seems to be an important quality when choosing a drug for the treatment of ICP because bile acid levels have been demonstrated to have a dose-dependent association with fetal complication rates. 10 In conflict with a previous report on dexamethasone therapy in ICP women, 16 we found the effects on pruritus and biochemical markers of cholestasis to be transient in the dexamethasone group. A rapid decrease in pruritus and bile acids was seen after the first week of treatment, but was followed by an increase.…”
Section: Discussioncontrasting
confidence: 55%
“…The reason for choosing only 1 week of active treatment followed by 2 weeks of placebo in the dexamethasone group was that this is the only dose regimen of dexamethasone treatment in ICP pregnancies previously reported in the literature. 16 Furthermore, questions have recently been raised concerning potentially harmful effects of corticosteroids on the developing fetal brain. This has lead to a more restrictive approach to corticosteroid treatment during pregnancy, 17,18 The data from the present study showed that dexamethasone was less effective than UDCA regarding all studied variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These benefits of dexamatosone is linked to its estrogen secretion inhibitor effects at placenta [47].But it is not preferred commonly, because it crosses placenta and may result adverse effects on the fetus at higher doses [48].…”
Section: Dexamethasonementioning
confidence: 99%
“…• Dexamethasone has also been used for treating ICP associated pruritis 62 . A recent randomized controlled trial comparing Dexamethasone to UDCA and placebo, however, found that dexamethasone was not effective in improving pruritis or ALT, and less effective than UDCA in decreasing bilirubin or bile acids levels 51 .…”
Section: Treatmentmentioning
confidence: 99%